Intervention for High School Latino Students in Preparing for College: Steps for Consideration. (July 2015) - Rodriguez, Eric; Rhodes, Kent; Aguirre, Geoffrey
Several factors contribute to a disproportionately lower Latino participation in college education. Foremost among those factors are policies that encourage quick job placement over career development, lack of understanding of the benefits of a college degree, lower expectations for Latino students, poor financial planning, and lack of guidance. A review of the literature shows that the strong work ethic imbued by Latino culture correlates with negative outcomes in college enrollment and completion. Therefore, intervention is required to create positive outcomes. Using Upward Bound as a model for intervention, several types of intervention and their effects are suggested and examined.